Narrative update of clinical trials with antihypertensive drugs in children and adolescents - Redón i Mas, Josep; Seeman, Tomas; Pall, Dénes; Suurorg, Lagle; Kamperis, Konstantinos; Erdine, Serap; Wühl, Elke; Mancia, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
To date, our knowledge on antihypertensive pharmacological treatment in children and adolescents is still limited because there are few randomized clinical trials (CTs), hampering appropriate management. The objective was to perform a narrative review of the most relevant aspects of clinical trials carried out in primary and secondary hypertension.
Gesehen am 09.11.2023